Future of Medicine with Artificial Intelligence - Dabadi, Sambardhan; Gajuryal, Sharad Hari (Annapurna Journal of Health Sciences, 2023)
Artificial Intelligence (AI) is one of the fastest growing technologies around the world. AI based system are capable of learning through various inputs provided to them and generate output based on their own analysis. These systems are substituting human effort and workload in various sectors, one of these sectors is healthcare and medicine as well. The use of such technologies have made decision making easier in some way, however there has been issues and problems associated with AI being used in medicine.